Diagnostic Role of Ultrasonography in Obstetrics and Gynaecology (TAJ: Journal of Teachers Association, 2018)
Ultrasonography (USG) is widely used in both gynaecology and obstetrics. USG has become an indispensable diagnostic tool. Specially in our developing country. Advanced US technologies, such as 3D sonography, provide powerful and highly accurate diagnostic tools. The clinical applications and uses of ultrasound include confirmation of pregnancy including multiple gestation, estimation of gestational age, localization of placenta and monitoring of foetal wellbeing. The others are evaluation of caesarean section scar integrity and post partum haemorrhage. Ultrasound is also useful in prenatal diagnosis of foetal anomaly. The clinical uses of ultrasound in gynaecology include diagnosis of uterine abnormality, ovarian tumour. Ovarian follicles follow up in infertility, diagnosis of ectopic pregnancy, evaluation of abortion case. Detection of pelvic mass & polycystic ovarian disease is also important. Ultrasound guided FNAC is also an important diagnostic tool.TAJ 2011; 24(2): 152-155